Changes in the cervical microbiota of cervical cancer patients after primary radio‐chemotherapy. Issue 9 (September 2020) - Tsakmaklis, Anastasia; Vehreschild, Maria; Farowski, Fedja; Trommer, Maike; Kohler, Christhardt; Herter, Jan; Marnitz, Simone
ABSTRACT : Objective : Several recent studies have identified a potential interaction between the vaginal microbiota and gynecological cancers, but little is known about the cervical microbiota and its changes during cancer treatment. Therefore, the aim of the study was to evaluate the quantitative and qualitative changes of cervical microbiota in patients undergoing concurrent chemotherapy and radiation treatment for locally advanced cervical cancer. Methods : Cervical cytobrush samples of 15 cervical patients undergoing chemoradiation treatment were collected 1 day before starting external beam radiation therapy and on the day of the last fraction of brachytherapy. After DNA extraction, 16S rRNA amplicon sequencing of the V3‐V4 region was performed on the MiSeq platform, followed by data processing and statistical analyses concerning the alpha and beta diversity of 16 samples (7 samples were excluded because of incomplete sample sets). Results : The amount of amplicon yield after polymerase chain reaction analysis in post‐radiation samples was significantly lower compared with the baseline samples (pre 31.49±24.07 ng/μl; post 1.33±1.94 ng/μl; p=0.007). A comparison of pre‐treatment and post‐treatment samples did not show significant differences regarding beta diversity (weighted UniFrac). There was no significant difference in alpha diversity, which is used to characterize species diversity within a particular community and takes into account both number and abundance (Shannon Diversity Index pre‐treatment samples: 2.167±0.7504 (95% CI 1.54 to 2.79); post‐treatment samples: 1.97±0.43 (95% CI 1.61 to 2.33); p=0.38). Interindividual differences in patients could partly explain some variation of the samples (permutational multivariate analysis of variance). Conclusion : There was a strong reduction in cervical bacterial loads after chemoradiation. Neither alpha nor beta diversity varied significantly when baseline samples were compared with post‐treatment samples.